Study on Cell Configuration Strategy and On-orbit Assembly of Heterogeneous Cells - LYU Jing-wei; GAO Yu-fei; DAI Ye; LIU Zhao-xu; QI Yun-shan; ZHANG Han-bo (Journal of Harbin University of Science and Technology)
Aiming at the problems of space facilities construction, based on the multi-level theory of robot system, four kinds of heterogeneous cell modules of space truss on-orbit assembly robots were designed, and a variety of robot configuration schemes for space truss on-orbit assembly were constructed. The kinematics simulation analysis was carried out for various space truss in-orbit assembly robots, and the relative trajectory curves of joint rotation and assembly motion were obtained during the truss assembly process. The kinematics experiment platform of the robot was built, and the causes of experimental errors were analyzed. The reliability of the robot motion performance and the accuracy of the truss assembly are verified, and the influence of the robot motion error and the truss assembly accuracy is discussed. The results of this study can provide a theoretical and technical support for the configuration and assembly of heterogeneous cell derived from space truss in-orbit assembly